2023
DOI: 10.1002/agm2.12250
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy and cumulative anticholinergic burden in older adults hospitalized with fall

Abstract: Introduction:Polypharmacy is a growing phenomenon associated with adverse effects in older adults. We assessed the potential confounding effects of cumulative anticholinergic burden (ACB) in patients who were hospitalized with falls. Methods:A noninterventional, prospective cohort study of unselected, acute admissions aged ≥ 65 years. Data were derived from electronic patient health records.Results were analyzed to determine the frequency of polypharmacy and degree of ACB and their relationship to falls risk. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…In a study by Montero Odasso et al it was reported risk for falls was increased by 12–16 % while the risk for incident falls was increased by 5–7% with each additional drug [ 33 ]. The correlation between falls and polypharmacy, in addition to being associated with multiple medication use, also appears to be attributable to PIMs, particularly in individuals taking anticholinergic medications [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Montero Odasso et al it was reported risk for falls was increased by 12–16 % while the risk for incident falls was increased by 5–7% with each additional drug [ 33 ]. The correlation between falls and polypharmacy, in addition to being associated with multiple medication use, also appears to be attributable to PIMs, particularly in individuals taking anticholinergic medications [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study on patients receiving palliative care, McNeill et al found PIM prevalence as 19 % [ 37 ]. In a Turkish study on patients receiving home care services, it was found that PIM prevalence was 53 % according to Beers criteria and 40 % according to the TIME-to-STOP criteria [ 34 ]. In a study about elderly patients receiving palliative care, Sevilla-Sanchez et al investigated PIM using STOPP-Frail criteria and found that there was at least one PIM in 67.2 % of the patients and that “inappropriate use of gastrointestinal system and metabolism medicines without clinic indication” was the most common PIM [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive effects represent one type of adverse effect associated with AC medication exposure. There are other adverse effects of AC medications in aging persons, however, including elevated risk for falls (Stewart et al, 2021;Wong et al, 2023) and mortality (Ali et al, 2020;Graves-Morris et al, 2020;Ruxton et al, 2015). Thus, in addition to probing the cognitive-related effects of AC medication use, future work should also investigate other health-related adverse effects associated with AC medications in autistic persons.…”
Section: Studymentioning
confidence: 99%
“…It is associated with numerous adverse effects, hospitalization, falls and mortality. 45,46 Polypharmacy predisposes to higher anticholinergic burden which may explain a proportion of the poor outcomes associated with it. 45…”
Section: The Evidencementioning
confidence: 99%
“…45,46 Polypharmacy predisposes to higher anticholinergic burden which may explain a proportion of the poor outcomes associated with it. 45…”
Section: The Evidencementioning
confidence: 99%